Eurasian Aerospace Defense: the Role of Strategic Nonnuclear Arms - A. I. Podberezkin (Vestnik MGIMO-Universiteta)
The article analyses the problem of non nuclear high precision conventional arms acquiring offensive and defensive functions. The author claims that by 2020 all strategic objects in Russian will be targeted by aerospace defense systems and there’s great probability that they might be destroyed by the first disarming strike of a potential adversary. The new stage of the scientific revolution having produced new high precision weapons has resulted not only in significant rearrangement of global political layout but also in radical changes in war strategy and has transformed the meaning of military power as a foreign policy tool. Once again it started to be used in minor and major conflicts and wars. The creation of the Eurasian Aerospace Defense depends on success of Eurasian integration processes in military sphere. The author believes that the second decade of XXI century might see a surprise major attack with strategic nonnuclear arms.